Deterrents in recruitment of COVID‐19 convalescent plasma donors: Experience from a hospital‐based blood centre in India. Issue 3 (21st March 2021) - Dhiman, Yashaswi; Coshic, Poonam; Pandey, Hem Chandra; Khatiwada, Basanta; Singh, Jasmeet; Mehta, Vikas; Gupta, Sanjay
Abstract: Introduction: Recruitment of Covid‐19 convalescent plasma (CCP) donors may present as a challenge due to inexperience and differences in donor profile as compared to whole blood donation. Present study highlights the deterrents to recruiting CCP donors at a hospital based blood centre. Materials and methods: Potential CCP donors were contacted individually by telephone and a group approach through camp organisers from May to July 2020. Recruitment challenges were noted and deferrals of these recruited donors during screening and medical examination was obtained and analysed. Results: Total 1165 potential CCP donors were contacted. Around 47% donors were lost due to challenges related to information storage and retrieval. Fear of health, family pressure, and fear of a new procedure were major reason (27.2%) for unwillingness to donate. The main reasons for deferral among potential donors were multiparity (38%) and being overage/underage (31.6%). Finally, 468 donors were recruited including 408 by individual approach and 60 by a group approach. From these absence of detectable COVID‐19 antibodies were found in 15.4%. Few donors (9.0%) were deferred as they had not completed 28 days post recovery. Conclusion: The process of CCP donor recruitment differs from that of whole blood donation and requires an individualised approach with involvement of clinicians in the initial phases of the pandemic. A group approach targeting specific organisations could be adopted for a successful CCP collection program. There is a need to relook into some aspects of donor selection such as consideration of multiparous female donors and overage/underage donors after reviewing scientific evidence.